2020
DOI: 10.36712/sdi.v27i2.9408
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Women from Domestic Violence: Islam, Family Law, and the State in Indonesia

Abstract: Despite the enactment of a specific law on domestic violence, the elimination of violence in the household is still an elusive target in Indonesia. A large number of Muslims’ divorces in the Religious Courts, for example, have involved domestic violence according to the National Commission on Anti Violence against Women. This article aims to discuss the opportunity and challenges of the elimination of domestic violence in the Indonesian Muslim Society. Employing both normative and socio-legal analysis, it find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
1
7
0
4
Order By: Relevance
“…Subordination of women in marriage has been the case in general as wives are considered economically unproductive and burdens upon their husband. 15 Underage marriage has numerous contributing factors, including not only economic and educational ones but also the values of marriage and gender embraced by society. Various studies have shown that economic factors significantly inform parents' decision to have their children marry early.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Subordination of women in marriage has been the case in general as wives are considered economically unproductive and burdens upon their husband. 15 Underage marriage has numerous contributing factors, including not only economic and educational ones but also the values of marriage and gender embraced by society. Various studies have shown that economic factors significantly inform parents' decision to have their children marry early.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
“…33 Women who marry at a young age are also more at risk for having an abortion, which adversely affects their fertility. 34 ICRW 35 reveals that underage mothers (aged [15][16][17][18][19] are twice as likely of dying from pregnancy-related complications. Nour 36 reports that women who marry at a young age are more vulnerable to sexually transmitted diseases, cervical cancer, and malaria.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
“…Every citizen and citizen has the right to work in decent conditions and for a fair wage." 49 This regulation is the legal foundation for allowing Tunisian women to work. In Tunisia, women are highly valued.…”
Section: Women Have the Right To Workmentioning
confidence: 99%
“…https://www.arabnews.com/node/1463806/middle-east, accessed on November 13, 2020. 49 The Constitution Republic Tunisia, Chapter II article 41, 2014. social attitudes, improved education and training for women, and legal protection concerning violence against women. 50 Women's social status is determined by the number of women, mostly in the public sector (public sector).…”
Section: Women Have the Right To Workmentioning
confidence: 99%
“…Article 6-16 contains the substantive rights and obligations of the Government. Article 17-30 contains provisions concerning institutional structure, procedures, and reporting mechanisms the implementation of convention ratification and accession the Convention, and in the event of a dispute regarding the application and interpretation of the Convention (Alfitri, 2020;Putra, 2019). There are some rules governing the protection of the child.…”
Section: Introductionmentioning
confidence: 99%